Anaphylaxis in children. (24th November 2020) - Tanno, Luciana Kase; Demoly, Pascal
Abstract: Anaphylaxis in children is a potential acute life‐threatening systemic hypersensitivity reaction. Anaphylaxis fatality rate is estimated to be 0.65% to 2%. Food is the main anaphylaxis trigger in children, notably cow's milk, peanuts, and tree nuts. Mucocutaneous manifestations are observed in more than 90% of cases, but it is not essential for diagnosis. Deaths are rather secondary to the laryngeal edema, observed in 40%‐50% of cases. Personal history of asthma, allergy to particular foods such as peanuts and tree nuts, and adolescence are known risk factors for anaphylaxis and more severe reactions. Epinephrine (adrenaline) is the medication of choice for the first‐aid treatment of anaphylaxis. However, adrenaline auto‐injectors (AAIs) are commercially available in only 32% of world countries. There are still considerable unmet needs in the field of anaphylaxis in children. Therefore, the Montpellier WHO Collaborating Centre aims to start the global action plan applied to anaphylaxis.